Simulation of Spray Injection in the Pressurizer Using RELAP5 - S. Dibyo; S Susyadi (Atom Indonesia, 2017)
A modeling research using Relap5 to assess the pressurizer of a pressurized water reactor(PWR) power plant has been performed. The heater and water injection systems in the pressurizer system of the PWRare of greatimportance for system pressure control.The heater is designed to increase the pressure while the water sprayer injection is to perform depressurization. Most of studies conducted in the past mainly focused on determining the effects of nozzle spray design and droplet size using testing loops. The purpose of this simulation is to analyze the spray injection flow rate against the pressure characteristics of the pressurizer using RELAP5. Through this approach, the optimum injection flow rate of full scale plant pressurizer can be analyzed. The parameters investigated are pressure and temperature.In RELAP5, the pressurizer tank wasmodeled with six volume nodes and the heater was modeled by using heat structure. In the model, the sprayer takes water from the cold leg to inject it into the top of tank region.The resultsshowedthat the mass flow of about 4 kg/s is the mosteffectivevalueto limit pressure in the pressurizer to below 15.7 MPa. However, the flow rates of 8 kg/s and more cause overpressure. This simulation is usefulto complement the data related to the water flow rate injection systems of the pressurizer.